Evaluación del extracto etanólico de Chamaesyce thymifolia como solución desinfectante natural en superficies inertes en contacto con alimentos - Sánchez Matos, Joselyn Lourdes (2022)
This work arose from the need to search for secondary metabolites from plants in the Peruvian Amazon to be studied as natural disinfectants. The objective was to verify the in vivo bactericidal effect of the ethanolic extract from Chamaesyce thymifolia on surfaces of slaughtered chicken vending tables of the Belen market house in Iquitos. The research design was explanatory, with a completely randomized factorial arrangement. The work was divided into three stages: obtainment of the ethanolic extract and its chemical components, in vitro antibacterial activity by disc diffusion, MIC/MBC, in vivo antibacterial activity by the count of viable aerobic mesophiles, and logarithmic reductions. The results show that the chemical components of the extract are abundant in triterpenes, steroids, phenols, and tannins; and moderately in alkaloids, lactones, and coumarins. The in vitro antibacterial activity by disc diffusion was sensitive for Staphylococcus aureus ATCC 25922 and intermediate for Enterococcus faecalis ATCC 29212, Pseudomonas aeruginosa ATCC 27853, Escherichia coli ATCC 25922, Escherichia coli ATCC 35218, Staphylococcus aureus ATCC 25923, Staphylococcus aureus ATCC 25923, Staphylococcus aureus ATCC 25923 ATCC 25923, and resistant to Salmonella typhimurium ATCC 14028. The MIC was between 2 to 8 mg/mL and the MBC between 32 and 128 mg/mL. The antimicrobial activity in vivo showed a high statistical significance (p<0.01) at a concentration of 16 mg/mL and a time of 30 minutes, the logarithmic reduction of the microbial count of the extract showed 99.9% efficacy. It is concluded that the ethanolic extract of Chamaesyce thymifolia can be used as a natural disinfectant on surfaces.